2022
DOI: 10.1097/aud.0000000000001196
|View full text |Cite
|
Sign up to set email alerts
|

Is Having Hearing Loss Fundamentally Different? Multigroup Structural Equation Modeling of the Effect of Cognitive Functioning on Speech Identification

Abstract: Objectives: Previous research suggests that there is a robust relationship between cognitive functioning and speech-in-noise performance for older adults with age-related hearing loss. For normal-hearing adults, on the other hand, the research is not entirely clear. Therefore, the current study aimed to examine the relationship between cognitive functioning, aging, and speech-in-noise, in a group of older normal-hearing persons and older persons with hearing loss who wear hearing aids. Design:We analyzed data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 71 publications
1
6
0
Order By: Relevance
“…The previously mentioned study by Marsja et al (2022) suggests impressively similar (if not identical) cognitive predictions from one hearing-impaired group compared to a normal-hearing group on a matrix sentence latent construct. This finding suggests a powerful generalization of the case that Cognitive Hearing Science—and the ELU model—applies to anyone, regardless of hearing status.…”
Section: Generalizationsmentioning
confidence: 70%
See 2 more Smart Citations
“…The previously mentioned study by Marsja et al (2022) suggests impressively similar (if not identical) cognitive predictions from one hearing-impaired group compared to a normal-hearing group on a matrix sentence latent construct. This finding suggests a powerful generalization of the case that Cognitive Hearing Science—and the ELU model—applies to anyone, regardless of hearing status.…”
Section: Generalizationsmentioning
confidence: 70%
“…Indeed, Gordon-Salant and Cole (2016) showed the same results to hold across age groups, with RST as part of the most prominent predictors. In the same vein, with large samples, Marsja et al (2022) used the n200 database ( Rönnberg et al, 2016 ) to study potential differences in cognitive involvement due to hearing loss. Marsja et al (2022) used a multi-group structural equation model (SEM) approach where the purpose was to assess whether the contribution of a “Cognition” latent variable (based on RST, a visuospatial WM test and a semantic WM word-pair test, and Raven’s matrices) was equally related to a SPIN criterion (Hagerman matrix sentences, Hagerman, 1982 ) for hearing-impaired hearing-aid users compared to normal-hearing participants.…”
Section: Recent Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Loughrey et al [ 82 ] used a meta-analysis of 36 studies and over 20,000 patients to show that age-related hearing loss is a significant predictor of a range of types of cognitive decline. However, even among older adults with normal hearing, cognitive performance predicts poor speech understanding; Marsja et al [ 9 ] used structural equation modeling on data from 399 older listeners (199 with and 200 without hearing loss) which indicated that cognitive performance was a strong predictor of speech understanding.…”
Section: Discussionmentioning
confidence: 99%
“…Previous experiments conducted in our laboratories and elsewhere have identified a set of psychophysical tasks of auditory processing (so-called “suprathreshold” auditory processing tests) that appear to predict performance on speech tasks with either noise or speech as the interference [ 2 , 3 , 4 , 5 , 6 , 7 ]. However, with a few notable exceptions—Rönnberg et al and Marsja et al [ 8 , 9 ]—most of these investigations have either explored no more than one or two auditory processing tasks at a time, or have lacked the statistical power to allow firm conclusions to be drawn (for an example, see Neher et al [ 7 ]) making it difficult to determine which independent predictors contribute most to speech-in-competition performance. To address the limitations of traditional laboratory-based psychophysical assessments of auditory processing ability, we developed a new assessment platform—Portable Automated Rapid Testing (PART)—that allows direct testing of a diverse range of auditory processing abilities and facilitates the collection of large data sets with consistent procedures.…”
Section: Introductionmentioning
confidence: 99%